A Study of Development of a Micro Hydro Turbine System with a Rim Drive and Air Injection Treatment for Cavitation. - (:unkn) unknown (My University, 2017)
This thesis presents the study of Kaplan hydro turbines system at a very low head and air injection treatment to reduce cavitation happening around a turbine. Regarding the study of Kaplan hydroturbine system, optimization of hydro turbine system with a rim generator to gain a better performance was conducted by CFD and experiment. E-Motors, the partner of this research, is developing an integrated design to simplify manufacturing and installation. The integrated design includes a rim in the outside of the turbine runner to house the electrical generator rotor, namely rim drive. This approach enables a compact and simple assembly without having shafts and outside generators, thus improving efficiency and facilitating assembly. Output power is limited due to experimental conditions, but CFD calculations showed good efficiency potential of this design. About the air injection treatment, the effect of air injected into a hydraulic system was investigated regarding power and reduction of cavitation. It was found that the air injection treatment can decrease cavitation over the blade and hub at most by 96.1% and 98.7%, respectively.
Keywords: Cavitation; CFD; Hydro Trubine; Renewable Energy